Venture capital financing, strategic alliances, and the initial public offerings of Internet startups - Chang, Sea Jin (Journal of Business Venturing, 2004)
This study examines how Internet startups' venture capital financing and strategic alliances affect these startups' ability to acquire the resources necessary for growth. Using the initial public offering (IPO) event as an early-stage measure for Internet startups' performance and controlling for the IPO market environment, this study found that three factors positively influenced a startup's time to IPO: the better the reputations of participating venture capital firms and strategic alliance partners were, the more money a startup raised, and the larger was the size of a startup's network of strategic alliances.